Evaluating the flow regulating functions of natural ecosystems in the Zambezi River Basin - McCartney, Matthew P.; Xueliang Cai; Smakhtin, Vladimir U. (International Water Management Institute, 2013)
By affecting evapotranspiration and influencing how water is routed and stored in a basin, forests, wetlands and floodplains play a crucial role in the hydrological cycle. Although they are widely attributed a major role in regulating flows (i.e., both attenuating floods and maintaining flow during dry periods), these services are rarely factored into the planning and management of water resources. One reason for the failure to include them is lack of understanding. Very often the extent to which natural regulating functions really occur is unclear. Against this background, this report describes a simple, pragmatic approach for quantifying the flow regulating functions of natural ecosystems. The method has been applied at 14 locations in the Zambezi River Basin.